Pemahaman Konsep Perubahan dan Kegunaan Benda dengan Metode Smart Game & Pembelajaran Kooperatif Tipe Make A Match dalam Mata Pelajaran IPA di SDN 12 Nan Sabaris - Suatri Suatri (Indonesian Institute for Counseling, Education and Therapy (IICET), 2015)
Results of preliminary observations at several elementary schools shows that there are some constraints faced by teachers in the learning process. One problem is difficult to cultivate an understanding of the concept of identifying objects are known and their usefulness to students through observation. The purpose of this action research are (1) to determine that the method of smart games and cooperative learning make a match can improve the understanding of the concept of identifying objects are known and their use through observation, (2) to improve the students' tasks in groups in understand the concept of identifying objects are known and their use through observation. Data obtained through tests and usage observation guide, the data is processed by a percentage. Results of the analysis of the data obtained in the first cycle of learning success; 64.00%, and the second cycle; amounting to 83.50%. So the smart methods of cooperative learning the game and make a match indicates no increase student learning from the first cycle to the second cycle. Thus the smart methods of cooperative learning the game and make a match can improve the understanding of the concept of identifying objects are known and their use through observation of students. The cooperation of students in completing the task in groups also increased, proved more active play looking for a partner in the group and the ability to group tasks more quickly and perfectly.